2022
DOI: 10.7759/cureus.31251
|View full text |Cite
|
Sign up to set email alerts
|

Thermography as a Breast Cancer Screening Technique: A Review Article

Abstract: Globally, breast cancer is the most frequently occurring cancer in women and is the reason for more disability-adjusted life years lost than any other type of cancer. Hence, early screening plays a vital role in reducing breast cancer mortality. Although mammography is the standard procedure used for screening and diagnosis of breast cancer, it still has some limitations. Other methods used for screening include ultrasound and clinical breast examination. Despite its limitations, mammography is the gold standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, currently, there is evidence of its good performance. 33,34 Thermography has already been included in the evaluation of vascular pathologies. In a study of thermography for thyroid nodules, Damião et al 35 found that malignant nodules have higher temperatures than their benign counterparts (33.46 °C vs. 33.01 °C).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, currently, there is evidence of its good performance. 33,34 Thermography has already been included in the evaluation of vascular pathologies. In a study of thermography for thyroid nodules, Damião et al 35 found that malignant nodules have higher temperatures than their benign counterparts (33.46 °C vs. 33.01 °C).…”
Section: Discussionmentioning
confidence: 99%
“…This mirrors the trend in the field of digital mammography, wherein the use of machine learning algorithms for extracting, detecting, characterizing and classifying radiomics features of mammograms has shown clinical benefit and are extensively used [23]. AI-enhanced breast thermography uses similar principles and is currently being re-evaluated at various centers as an ancillary modality in the screening and diagnosis of breast disease (24,25). In this paper, we have compared the performance of an automated breast thermography interpretation tool called Thermalytix that uses a combination of domain knowledge and data analytics for interpretation of thermal images, with the manual interpretation of the thermal images by an expert thermologist in the detection of breast cancers.…”
Section: Introductionmentioning
confidence: 93%
“…The algorithm then classifies the datasets and obtains a final result. The combination of modern cameras and advanced algorithms is the basis for the renewed interest in thermography to detect breast cancer (24,25).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Sin embargo, actualmente existe evidencia de su buen desempeño. 33,34 La termografía ya se ha incluido en la evaluación de patologías vasculares. En un estudio sobre termografía en nódulos tiroideos, Damião et al 35 encontraron que los nódulos malignos tienen temperaturas más altas que los benignos (33.46 °C versus 33.01 °C).…”
Section: B C Aunclassified